2001
DOI: 10.1159/000050674
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Lansoprazole, Amoxycillin, and Clarithromycin versus Lansoprazole, Bismuth, Metronidazole and Tetracycline in the Retreatment of Patients Failing Initial <i>Helicobacter pylori</i> Therapy

Abstract: Background/Aim: 10–30% of the patients treated for Helicobacter pylori fail to clear the infection after initial therapy. Little is known as to the efficacy of retreatment regimens in these patients. Proton pump inhibitor (PPI) -based triple and quadruple therapies demonstrate efficacies of 80–90% as initial therapy for H. pylori infection, but whether these regimens are as effective when used for retreatment is unknown. The efficacy of a metronidazole-containing regimen in this situation is also unknown. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
(17 reference statements)
0
21
0
1
Order By: Relevance
“…Th e pooled eradication rate for 14-day bismuth quadruple therapy was 80% (95% CI 76-84%), and was signifi cantly higher among Asian studies (82%; 77-86%) compared with European or US studies (74%; 68-81%). in the United States study ( 177 ), the overall eradication rate for 14-day bismuth quadruple therapy was 71%, but diff ered substantially among patients who had previously failed bismuth quadruple treatments for 7-14 days (eradication rate 53%; 28-77%) and the patients who had previously failed triple or dual clarithromycin-based treatments without bismuth (eradication rate 100%; 72-100%).…”
Section: Bismuth-quadruple Regimenmentioning
confidence: 97%
See 1 more Smart Citation
“…Th e pooled eradication rate for 14-day bismuth quadruple therapy was 80% (95% CI 76-84%), and was signifi cantly higher among Asian studies (82%; 77-86%) compared with European or US studies (74%; 68-81%). in the United States study ( 177 ), the overall eradication rate for 14-day bismuth quadruple therapy was 71%, but diff ered substantially among patients who had previously failed bismuth quadruple treatments for 7-14 days (eradication rate 53%; 28-77%) and the patients who had previously failed triple or dual clarithromycin-based treatments without bismuth (eradication rate 100%; 72-100%).…”
Section: Bismuth-quadruple Regimenmentioning
confidence: 97%
“…Aft er 2000, three RCTs in the United States or Europe assessed triple therapy with a PPI, clarithromycin, and amoxicillin as a second-line treatment ( 177,198,199 ), while none assessed triple therapy replacing amoxicillin with metronidazole as a second-line treatment. In a US RCT by Magaret et al ( 177 ), patients who had failed one of several fi rst-line treatments for H. pylori were randomized to 14-day PAC or 14-day bismuth quadruple therapy.…”
Section: Clarithromycin Triple Therapymentioning
confidence: 99%
“…With this therapy, some authors [45] have achieved H pylori eradication in 85% of cases, while others have reported success rates of 86% [125] or even 100% [126] . In favor of this strategy is the study by Magaret et al [127] , who studied a group of 48 patients after failure of previous H pylori therapy with a metronidazolecontaining regimen, and randomized them to either lansoprazole, amoxicillin and clarithromycin twice daily for 14 d, which is the logical approach with triple therapy not repeating metronidazole, or to lansoprazole, bismuth, metronidazole and tetracycline for 14 d, which is the quadruple therapy repeating metronidazole. Intentionto-treat efficacies were 75% for a triple regimen and 71% for a quadruple.…”
Section: Rbc Tetracycline and Metronidazolementioning
confidence: 99%
“…With this therapy, some authors [Gisbert et al 1999a] have achieved H. pylori eradication in 85% of cases, while others have reported success rates of 86% [Reilly et al 1995] or even 100% [Lerang et al 1997]. In favor of this strategy is the study by Magaret et al [2001], who studied a group of 48 patients after failure of previous H. pylori therapy with a metronidazole-containing regimen, and randomized them to either lansoprazole, amoxicillin and clarithromycin twice daily for 14 days (i.e. the logical approach with triple therapy not repeating metronidazole), or to lansoprazole, bismuth, metronidazole and tetracycline for 14 days (i.e.…”
Section: Introductionmentioning
confidence: 99%